(untitled) (Bioscience Journal, 2018)
This work aimed to correlate treatments using fungicides to different vegetation indices in response to effects caused by ramularia leaf spot (Ramularia areola). The experiment was carried out in the municipality of Chapadão do Sul, state of Mato Grosso do Sul, in the harvest 2016/2017, and consisted of a randomized blocks design, with 17 treatments and four replications. Data were obtained from the Sequoia 4.0 passive sensor and the Green Seeker LT 200 active sensor. From the information recorded by the sensors, nine vegetation indices were generated and compared with the area under the curve of disease progression, plant height, yield, and agronomic efficiency, in 17 different treatments of fungicide products. Treatments responded differentlyÂ to the product applied. The SAVI index (Soil Adjusted Vegetation Index), obtained from the band in the red spectral range, presented higher correlation to AACPD, agronomic efficiency, and yield. The NDVI index (Normalized Difference Vegetation Index) had a higher correlation to plant height and SR (simple ratio), both using the wavelength in the red spectral range.